Manajemen Ekstubasi pada Pasien dengan Jalan Nafas Sulit Perioperatif - Adiyanto, Bowo; Jufan, Akhmad Yun; Adiyatma, Krisna Hario (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Tracheal extubation is a critical step during emergence from general anesthesia. Good management of extubation is needed to prevent undesired complication including laryngospasm, hypoxia, airway injury. Patient with difficult airway is at risk during intubation and extubation period, so the knowledge about it is necessary.